Strengthening Human Resources as Lecturers Through the E-Learning Learning Method - Agus Supinganto; Suharmanto; Irwan Budiana; Kusniyati Utami (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: The concept of e-learning is an alternative for students who are unable to attend faceto-face lectures. The use of e-learning as an alternative learning is increasing in line with technologicaldevelopments. Aim: This study applies e-learning learning methods to strengthen educational humanresources as lecturers using Computer-based Multimedia Communication (CMC). Method: Thisresearch is a pre-experimental study. The research was conducted in STIKes Yarsi Mataram, Indonesiain 2020. The measuring instrument used a questionnaire. The study population was all students, witha total sample of 81 students. The independent variables include a method of learning. The dependentvariable in this study was knowledge. The analysis used was univariate and bivariate using paired t-test.Result and Discussion: frequency of e-learning based on CMC in the experimental group, namely 63%in the evaluation and 80% in the implementation process. While in the control group using conventionalmethods, 50% of the intervention and 23% of the implementation. Conclusion: Improving studentlearning outcomes in the community nursing process by using the CMC learning method is moreeffective than using conventional methods.